2014
DOI: 10.2147/ijn.s71586
|View full text |Cite
|
Sign up to set email alerts
|

Nanovector-based prolyl hydroxylase domain 2 silencing system enhances the efficiency of stem cell transplantation for infarcted myocardium repair

Abstract: Mesenchymal stem cell (MSC) transplantation has attracted much attention in myocardial infarction therapy. One of the limitations is the poor survival of grafted cells in the ischemic microenvironment. Small interfering RNA-mediated prolyl hydroxylase domain protein 2 (PHD2) silencing in MSCs holds tremendous potential to enhance their survival and paracrine effect after transplantation. However, an efficient and biocompatible PHD2 silencing system for clinical application is lacking. Herein, we developed a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…After transplant PHD2 siRNA-modified MSC in myocardial infarction models, MSC survival and paracrine function of IGF-1 were enhanced significantly in vivo, with decreased cardiomyocyte apoptosis, scar size, and interstitial fibrosis, and increased angiogenesis in the diseased myocardium, which ultimately attenuated ventricular remodeling and improved heart function. This study demonstrated that a great potential of siRNA-modified stem cells in therapeutic applications, which, of course, might be used in AKI [73].…”
Section: Sirna-modified Stem Cell Therapymentioning
confidence: 71%
“…After transplant PHD2 siRNA-modified MSC in myocardial infarction models, MSC survival and paracrine function of IGF-1 were enhanced significantly in vivo, with decreased cardiomyocyte apoptosis, scar size, and interstitial fibrosis, and increased angiogenesis in the diseased myocardium, which ultimately attenuated ventricular remodeling and improved heart function. This study demonstrated that a great potential of siRNA-modified stem cells in therapeutic applications, which, of course, might be used in AKI [73].…”
Section: Sirna-modified Stem Cell Therapymentioning
confidence: 71%
“… M2 polarization↑; Inflammation, infarct size and fibrosis↓;(Masson’s trichrome) Post-MI heart failure and mortality↓ [ 203 ] Lipidoid NPs IFR5 siRNA ApoE-/- mice; LCA i.v. MMP9/TIMP1↓; healing ↑; HF↓ [ 204 ] Arginine-terminated generation 4 poly(amidoamine) (Arg-G4) 152.2±18.5 nm PHD2 siRNA Mice; LCA Intramyocardial injection of Arg-G4-siRNA transfected MSCs LVEF and LVFS; Infarct area↓; Survival↑ [ 205 ] Abbreviations: eGFP, enhanced green fluorescent protein; PGEA, ethanolamine-modified poly(glycidyl methacrylate); PFBT, poly(9,9-dioctylfluorene-alt-benzothia-diazole); DSPE, 1.2-distearoyl-sn-glycero-3-phosphoethanolamine; CPP, cell-penetrating peptide; PMSNs, photoluminescent mesoporous silicon nanoparticles; PEI, polyethylenimine; MSC, mesenchymal stem cell; AT1R, angiotensin II type 1 receptors; Sdf1, stromal-derived factor 1; CRMP, collapsin response mediator protein; HR1, human Relaxin-expressing plasmid DNA with hypoxia response element 12 copies; IRF5, interferon regulatory factor 5; CO, cardiac output. …”
Section: The Advanced Nanotherapeutic Strategies For Myocardial Infarctionmentioning
confidence: 99%